2014
DOI: 10.1590/s0100-06832014000300035
|View full text |Cite
|
Sign up to set email alerts
|

Valores de referência de qualidade para metais pesados em solos do Rio Grande do Norte

Abstract: O crescimento industrial e o populacional têm aumentado os teores de metais pesados nos solos e impactado a qualidade desse recurso. Nesse contexto, as agências de proteção ambiental vêm despendendo esforços para o estabelecimento de índices que possam identificar áreas suspeitas de contaminação. Valores de Referência de Qualidade para Solos (VRQs) refletem a concentração natural de determinada substância no solo, sem interferência antrópica. O trabalho objetivou estabelecer os VRQs para os metais Ag, Ba, Cd, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 15 publications
2
11
1
8
Order By: Relevance
“…Data on soil background concentrations of trace (Salonen and Korkka-Niemi, 2007;Biondi et al, 2011;Preston et al, 2014;Alfaro et al, 2015) and major elements (Montserrat and Camarero, 2010;Hannan and Tanguma, 2012;Dantu, 2014) are easily found in the literature. However, data regarding REEs are comparatively scarce and have mainly focused on determination of REEs in a limited number of soil types (Turra et al, 2011;Damascena et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Data on soil background concentrations of trace (Salonen and Korkka-Niemi, 2007;Biondi et al, 2011;Preston et al, 2014;Alfaro et al, 2015) and major elements (Montserrat and Camarero, 2010;Hannan and Tanguma, 2012;Dantu, 2014) are easily found in the literature. However, data regarding REEs are comparatively scarce and have mainly focused on determination of REEs in a limited number of soil types (Turra et al, 2011;Damascena et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Minas Gerais (Minas Gerais, 2011), Espírito Santo (Payes et al, 2010), Rio Grande do Norte (Preston et al, 2014) (Payes et al, 2010); e Rio Grande do Norte (Preston et al, 2014) Corroborando com outros estudos em várias matrizes (Olise et al, 2005;Stosnach, 2005;Cinosi et al, 2010;Amberger et al, 2010;Alov, 2011;Cataldo, 2012), houve correlação linear positiva entre os teores dos elementos analisados determinados por FAAS/GFAAS e TXRF, sendo os coeficientes de correlação de Pearson, r, (p<0,01) iguais a: Pb (0,7); Cr (0,7); Mn (0,7); Ni (0,5); Cu (0,6); Zn (0,5); e As (0,5). Dessa maneira, o uso de TXRF para determinar esses elementos em amostras de solo para fins de caracterização de contaminação é interessante, haja vista a simplicidade e rapidez no preparo das amostras e ao fato de não serem necessários procedimentos de ataque ácido nas amostras para a extração dos ET.…”
Section: Resultsunclassified
“…The differences among the QRVs for each soil show how challenging the establishment of a single and generic QRV for such diverse environments will be. The results clearly showed the need for determining a soil-type specific QRV, as similarly recommended for heavy metals in soils by Santos and Alleoni (2013 (Cetesb, 2001;Caires, 2009;Santos and Alleoni, 2013;Preston et al, 2014), while few studies suggested QRVs based on the 90 th percentile (Paye et al, 2010;Almeida Júnior, 2016 (Table 7). The vast difference between the percentiles highlights that the establishment of QRVs based on the 75 th percentile can significantly restrict the assessment.…”
Section: Quality Reference Values (Qrvs) Of Radionuclidesmentioning
confidence: 93%